Ex vivo biomechanical evaluation of Acute lumbar endplate injury and comparison to annulus fibrosus injury in a rat model. (July 2022) - Wang, Dalin; Lai, Alon; Gansau, Jennifer; Nasser, Philip; Lee, Yunsoo; Laudier, Damien M.; Iatridis, James C.
Abstract: Back pain is often associated with intervertebral disc (IVD) degeneration, and IVD degeneration phenotypes are commonly characterized by annulus fibrosus (AF)-driven and endplate (EP)-driven phenotypes. Few studies of EP injury exist in animal models, even though clinical studies show EP lesions are strongly associated with IVD pathology and pain. This project established an ex-vivo rat lumbar EP injury model and characterized effects of EP injury on motion segment biomechanical properties, as compared to AF injury, a common way of inducing IVD degeneration. Lumbar motion segments (39 total vertebra-IVD-vertebra sections) assigned to Intact (L1/L2), AF injury and EP injury (L3/L4 and L5/L6 randomly selected), and biomechanically tested in axial tension-compression, stress-relaxation and torsional testing in pre-injury and post-injury conditions using a repeated-measures design. EP injury involved superior vertebra endplate puncture transcorporeally and obliquely. AF injury involved mid-line punctures anterior and bilaterally. Axial ROM, tensile stiffness, hysteresis, and neutral zone stiffness were significantly affected by EP injury but not AF injury. Torque range, torsional stiffness and torsional neutral zone stiffness were significantly affected by AF injury but not EP injury. Stress-relaxation fast time constant was decreased for EP injury. EP and AF injuries induced distinct biomechanical changes in lumbar motion segments with EP injury having the largest impact on axial biomechanical properties and AF injury most prominently affecting torsional properties. This study deepens the understanding of biomechanical mechanism of EP-driven low back pain and provides methods and biomechanical characterization for future in vivo studies. Graphical abstract: Image 1 Highlights: Few animal models of EP injury exist, even though clinical studies show EP defects are a significant source of pain. Ex-vivo rat lumbar EP injury model was used to characterize effects of EP defects defects on motion segment biomechanical behaviors. EP injury altered axial ROM, tensile stiffness, hysteresis, neutral zone stiffness, and stress relaxation time constant. EP injury mostly impacted axial biomechanical properties while AF injury mostly affected torsional properties.